Bells of Conquest; the life of St. Bernard of Clairvaux. - Daughters of St. Paul. ([Boston] St. Paul Editions, 1968)
Recounts the life of St. Bernard of Clairvaux and his lifelong struggle to attain true saintliness in the image of Christ.
Keywords: Hagiography (3SjQ hbUU GdTNUjGJ GdeSjMjIs; History -- Christian saints -- France -- Biography -- Juvenile literature